PENCEGAHAN PERUNDUNGAN DENGAN KONSEP TAZKIYATUN NAFS DALAM PENDIDIKAN AGAMA ISLAM - Simanullang, Malik; Ainurrafiq, Ainurrafiq; Taufik Abdillah Syukur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to discuss bullying prevention using the concept of tazkiyatun nafs (self-purification) in Islamic religious education. Therefore, this study uses a qualitative method with a library approach. Therefore, the researcher uses references relevant to this study to ensure the results are in accordance with the desired results. The results of this study indicate that tazkiyatun nafs is the process of purifying the soul by carrying out all of Allah's commands and avoiding all His prohibitions. Therefore, there are three methods used: Takhalli, or removing and cleansing our souls from bad traits; Tahalli, or infusing and adorning our souls with praiseworthy qualities; and Tajalli, or the results of the takhalli and tajalli processes so that we feel close to Allah SWT. Therefore, the most fundamental tool used in this concept is prayer. Therefore, the conclusion is that tazkiyatun nafs has a very positive influence in preventing bullying in Islamic religious education